Formation of the methodology of exercise equipment application in the motion abilities development and health strengthening of schoolchildren and place of application of such equipment in the modern system of physical training. - Казанцева [Ganna Kazantseva], Ганна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> There have been considered the historical aspects of forming and development of the method of usage of technical devices (exercise machines) in educational-training and correctional-health work with children. There have been disclosed the advantages of inclusion of exercises with fitness equipment into the system of traditional sports lessons at school. There have been given and described the scientific achievements, that comprise the physiological fundamentals of method (general biological concept of kinesophilia, theory of tiredness and recovery, theory of motive-visceral reflexes). There has been shown the reasonability of the use of innovative equipment and special stock in practical activity in physical education of pupils of different age groups, and also the prospect of realization of the principle of individual approach concerning pupils with poor health and reduced functional possibilities. There has been pointed the place of the considered method in the modern system of pedagogical influence. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->